DOMAIN NAME AS INTANGIBLE PROPERTY RIGHTS IN THE PERSPECTIVE OF INDONESIAN LAW - Galang Fauzan Prawinda; Trisadini Prasastinah Usanti; Ghansham Anand (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This study aims to examine (1) the Position of Domain Names as Intangible Objects in Indonesian National Law; (2) Legal Protection for Domain Name Owners according to Indonesian Laws and Regulations. This study employs normative legal research using a statutory approach. The legal sources used in this study include primary legal materials and secondary legal materials using the technique of collecting legal materials through document studies and analyzed using deductive method. The results of this study show that (1) Domain names in the development of Indonesian civil law can be understood as objects of modern law, but they do not meet the elements of objects that can be controlled by property rights because their power still depends on the registration period. (2) Legal protection for domain names is provided preventively through regulatory registration mechanisms, the application of the principles of first come, first served, and the obligation to use in good faith, as well as repressively through civil lawsuits and dispute resolution managed by PANDI through PPND (Domain Name Dispute Resolution). However, such protection is still limited because the rights to domain names born from registration are administrative and contractual.